1997
DOI: 10.1021/jp963337p
|View full text |Cite
|
Sign up to set email alerts
|

A Combined in-Situ PM-RAIRS and Kinetic Study of Single-Crystal Cobalt Catalysts under Synthesis Gas at Pressures up to 300 mbar

Abstract: The coadsorption behavior of CO and hydrogen on Co(0001) during exposure to mixtures of H2 and CO at pressures up to 300 mbar and temperatures between 298 and 490 K has been studied by in-situ polarization modulation reflection absorption infrared spectroscopy (PM-RAIRS). At 490 K it is shown that adsorbed CO molecules attached to cobalt atoms at step edges (“defect sites”) disappear. We explain this observation in terms of hydrocarbon formation at defect sites, which blocks the adsorption of CO at these posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 43 publications
10
88
0
1
Order By: Relevance
“…Surface roughening of smooth single crystal surface induced by CO and H 2 has been reported for Pt and Rh 53 as well as Co. [54][55][56] Hence, we speculate that the surface planes on Ru nanoparticles greater than 4 nm are large enough to accommodate further layers of Ru giving rise to increased density of step-edge sites. Although the present data clearly confirm that the performance most strongly depends on particle size and not on the Ru 0 content, it remains to be determined how the exact synthesis conditions affects the surface composition of the nanoparticles.…”
Section: 8supporting
confidence: 60%
“…Surface roughening of smooth single crystal surface induced by CO and H 2 has been reported for Pt and Rh 53 as well as Co. [54][55][56] Hence, we speculate that the surface planes on Ru nanoparticles greater than 4 nm are large enough to accommodate further layers of Ru giving rise to increased density of step-edge sites. Although the present data clearly confirm that the performance most strongly depends on particle size and not on the Ru 0 content, it remains to be determined how the exact synthesis conditions affects the surface composition of the nanoparticles.…”
Section: 8supporting
confidence: 60%
“…C 1 coupling reaction on both flat and stepped Co surfaces and the comparison between the reactions on the flat and stepped surfaces clearly showed that FT reactions mainly occur at surface steps [24]. This is supported by experimental work: (i) CO adsorptioninduced surface restructuring on flat Co(0001) was observed by Wilson and de Groot under FT reaction conditions using STM [50], and up to 50% of surface Co atoms were found to be located at the step edge sites; and (ii) by monitoring CO adsorption on Co(0001) with and without the presence of H 2 using in situ PM-RAIRS, Beitel et al [51,52] found that hydrocarbons are formed at CO adsorption-induced step sites.…”
Section: Active Sitementioning
confidence: 64%
“…CO reaction at 500 K, provided that the C coverage is comparable to the CO coverage. Although CO is found to be the most abundant surface intermediate on the Co surface, experimental work [51,52] showed that adsorbed carbonaceous species crowd at step sites under typical FT reaction conditions. Thus, one may expect that the CO coverage is unlikely to be three orders of magnitude greater than the C atom.…”
Section: Why Carbene Mechanism?mentioning
confidence: 99%
“…The model catalysts were prepared by deposition of a thin TiO 2 film on a Ru(0001) substrate and subsequent evaporation of Au, which produces surfaces with similar Au particle sizes as typically obtained for dispersed Au/TiO 2 catalysts [11]. The interaction of these model systems with CO was mainly studied by in-situ IR, employing polarizationmodulation techniques, which allows the performance of in-situ IR measurements under pressures up to almost atmospheric pressure [12,13]. These in-situ measurements are complemented by ex-situ XPS measurements, performed before and after the high pressure interaction with CO.…”
Section: Introductionmentioning
confidence: 99%